Policy for innovative entrepreneurship: Institutions, interventions, and societal challenges - Bradley, Steven W.; Kim, Phillip H.; Klein, Peter G.; McMullen, Jeffery S.; Wennberg, Karl (Strategic Entrepreneurship Journal, 2021)
Research Summary Innovative entrepreneurship, defined as the creation of new products, services, production methods, or business models, is critical for firm, industry, and economic growth and a key determinant of societal well‐being. This special issue explores the roles of institutions and government policies in promoting or impeding innovative entrepreneurship. In this introductory editorial, we review theory and evidence on entrepreneurship at the macro‐institutional and micro‐policy levels, highlighting costs and benefits of alternative institutional environments and targeted policy interventions, as well as interactions within and across levels. We summarize the six papers in the special issue, discuss their contributions to the literature, and suggest how future work can build upon these and other papers to advance our understanding of the conditions and mechanisms underlying successful entrepreneurial innovation. Managerial Summary Innovation and entrepreneurship bring new products and services to market, help firms and industries to grow, and generate improvements in social and economic life. The papers in this special issue explore the background conditions—laws, political processes, regulations, tax policy, subsidies, training programs, and more—that make entrepreneurship and innovation successful. Both “macro” and “micro” policies can stimulate successful entrepreneurial and innovative outcomes, but can also become politicized, be ineffective, and generate unintended consequences. The papers offer lessons to researchers, policymakers, and practitioners about making entrepreneurship and innovation more successful.